2015
DOI: 10.1007/s00128-015-1627-0
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Kresoxim-Methyl in Water: Impact of Varying pH, Temperature, Light and Atmospheric CO2 Level

Abstract: In the present investigation, persistence of kresoxim-methyl (a broad spectrum strobilurin fungicide) was studied in water. Results revealed that kresoxim-methyl readily form acid metabolite. Therefore, residues of kresoxim-methyl were quantified on the basis of parent molecule alone and sum total of kresoxim-methyl and its acid metabolite. In water, influence of various abiotic factors like pH, temperature, light and atmospheric carbon dioxide level on dissipation of kresoxim-methyl was studied. The half life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Differing from the other strobilurin fungicides such as azoxystrobin , and kresoxim-methyl, 1 possesses a unique methoxyacetamide moiety instead of the conventional methoxyacrylate or methoxyiminoacetate structure. The absence of acrylate or imino double bond in 1 resulted in the differential photodegradation profiles in water.…”
Section: Discussionmentioning
confidence: 99%
“…Differing from the other strobilurin fungicides such as azoxystrobin , and kresoxim-methyl, 1 possesses a unique methoxyacetamide moiety instead of the conventional methoxyacrylate or methoxyiminoacetate structure. The absence of acrylate or imino double bond in 1 resulted in the differential photodegradation profiles in water.…”
Section: Discussionmentioning
confidence: 99%
“…AZOX concentration decreased with time for all formulations, and all degradation kinetics followed a first-order model (Figure and Table ; R > 0.9876, P < 0.05). Hydrolysis is expected to be the main degradation mechanism at pH 8 . The first-order degradation rate constant ( k ) determined from the slope (absolute value) of the linear fit ranged from 0.0026 ± 0.0002 min –1 for the conventional formulation to 0.0028 ± 0.0002 min –1 for AZOX encapsulated in nSiO 2 , and to 0.002 ± 0.0002 min –1 for AZOX encapsulated in Allosperse.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis is expected to be the main degradation mechanism at pH 8. 35 The first-order degradation rate constant (k) determined from the slope (absolute value) of the linear fit ranged from 0.0026 ± 0.0002 min −1 for the conventional formulation to 0.0028 ± 0.0002 min −1 for AZOX encapsulated in nSiO 2 , and to 0.002 ± 0.0002 min −1 for AZOX encapsulated in Allosperse. In the equation, the slope for the Allosperse (0.002) was significantly lower than that of the conventional pesticide (0.0026) or nSiO 2 (0.0028).…”
Section: Thermal Degradation Kinetics Of Azoxystrobin Inmentioning
confidence: 98%
“…Azoxystrobin metabolism is similar to the degradation of methoxyiminoacetate (Balba, 2007) and the fate of trifloxystrobin in plants and kresoxim-methyl in soils, plants, and rats. Khandelwal et al (2016) and light in aqueous conditions and revealed that it readily forms acid metabolites. The study emphasized that abiotic factors have significant effects on the dissipation of kresoxim-methyl under aqueous conditions.…”
Section: Physicochemical Transformation Of Strobilurinsmentioning
confidence: 99%
“…found that the photochemical reactivity of azoxystrobin was enhanced as the solvent polarity decreased. This phenomenon indicates that the accumulation of azoxystrobin tends to occur inside the cuticle, where it is photodegraded, or at the surface of crop leaves.Azoxystrobin metabolism is similar to the degradation of methoxyiminoacetate(Balba, 2007) and the fate of trifloxystrobin in plants and kresoxim-methyl in soils, plants, and rats Khandelwal et al (2016). investigated the persistence of kresoximmethyl at different temperatures, pH, atmospheric CO 2 levels…”
mentioning
confidence: 99%